2013
DOI: 10.5051/jpis.2013.43.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Role of collagen membrane in lateral onlay grafting with bovine hydroxyapatite incorporated with collagen matrix in dogs

Abstract: PurposeThe objective of this study was to elucidate the role of collagen membranes (CMs) when used in conjunction with bovine hydroxyapatite particles incorporated with collagen matrix (BHC) for lateral onlay grafts in dogs.MethodsThe first, second, and third premolars in the right maxilla of mongrel dogs (n=5) were extracted. After 2 months of healing, two BHC blocks (4 mm×4 mm×5 mm) were placed on the buccal ridge, one with and one without the coverage by a CM. The animals were sacrificed after 8 weeks for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…) or using the same experimental protocol in the same model but without loading of rhBMP‐2 (Jung et al. ). The histometric analysis indicated that the BRC ratio was significantly lower in the CM group than in the BHC group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) or using the same experimental protocol in the same model but without loading of rhBMP‐2 (Jung et al. ). The histometric analysis indicated that the BRC ratio was significantly lower in the CM group than in the BHC group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results from our previous study (Jung et al. ) were employed in this study to avoid repeated experiments and overuse of animals. Therefore, despite these ethical issues, further studies including a large‐scale experiment using another extensive augmentation model are needed to confirm the present results.…”
Section: Discussionmentioning
confidence: 99%
“…While the block-shaped biomaterial can maintain its structure without the aid of an additional barrier membrane, Jung et al recommended using a barrier membrane in bone augmentation procedures, especially when the defect is unfavorable (Jung et al 2013). Moreover, Adeyemo et al found that the effect of collagen membrane coverage on bone graft volume maintenance was dependent on the membrane stability during the healing period (Adeyemo et al 2008).…”
mentioning
confidence: 96%
“…The non-cross-linked collagen in BHC attributes to maintain the block shape of BHC and degrades within 1-2 weeks. Jung et al reported that the BHC could be used successfully in a lateral onlay graft model when combined with collagen membrane, whereas the BHC collapsed and failed to maintain the augmented space when collagen membrane was not used (Jung et al 2013).…”
mentioning
confidence: 98%
“…This combination provides the material with enough flexibility and compression capability to improve both the clinical handling and the adaptation to the bone defect (Jung et al. ).…”
mentioning
confidence: 99%